The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/15472450.2013.856714
|View full text |Cite
|
Sign up to set email alerts
|

Quantified Traveler: Travel Feedback Meets the Cloud to Change Behavior

Abstract: We describe the design and evaluation of a system named Quantified Traveler (QT). QT is a Computational Travel Feedback System. Travel Feedback is an established programmatic method whereby travelers record travel in diaries, and meet with a counselor who guides her to alternate mode or trip decisions that are more sustainable or otherwise beneficial to society, while still meeting the subject's mobility needs. QT is a computation surrogate for the counselor. Since counselor costs can limit the size of travel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 22 publications
0
81
1
4
Order By: Relevance
“…Hence, the factors that maximize behavioural change according to various behavioural theories (goal setting, social comparison) are not uniformly appreciated by participants, and may potentially lead to drop out or not signing up. Finally, a contradiction was reported between the consortium's aim to change participants' behaviour but also their attitudes, and participants' autonomous decision making (Jariyasunant et al 2015). Direct questions regarding the effects of fossil fuels on greenhouse effect, asked before and after the study, showed a decline in reported awareness.…”
Section: Contradictions and Developmentsmentioning
confidence: 95%
See 2 more Smart Citations
“…Hence, the factors that maximize behavioural change according to various behavioural theories (goal setting, social comparison) are not uniformly appreciated by participants, and may potentially lead to drop out or not signing up. Finally, a contradiction was reported between the consortium's aim to change participants' behaviour but also their attitudes, and participants' autonomous decision making (Jariyasunant et al 2015). Direct questions regarding the effects of fossil fuels on greenhouse effect, asked before and after the study, showed a decline in reported awareness.…”
Section: Contradictions and Developmentsmentioning
confidence: 95%
“…Travellers may be compared to the average of the other participants (sometimes called the community), or to self-set goals. In this section, we discuss the activity system based on a number of reported studies of travel feedback apps (Gabrielli and Maimone 2013;Wells et al 2014;Broll et al 2012;Meloni and di Teulada 2015;Jariyasunant et al 2015;Brazil et al 2013). …”
Section: Travel (And Activity) Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies has focused on the recording and analysis of mobility and activity data using smartphones, usually by utilizing location (GPS) and accelerometer data ( [18], [19], [20], [21], [22], [23], [24], [25], [26]). Issues such as suitability of sensors for activity recognition [27], accuracy of transport mode classification [28], [29] and energy consumption of the app [30] are well researched areas.…”
Section: Large Scale Automatic Mobility Monitoringmentioning
confidence: 99%
“…The measures reported back to subjects often include reports, per mode, of quantifiable aspects such as cost, calories consumed or CO 2 produced [8].…”
Section: Introductionmentioning
confidence: 99%